Charles Darwin and ecological explanations of biotic invasions: a historical analysis and modern concepts - Mosyakin, A.S. (Український ботанічний журнал, 2009)
The contribution of Ch. Darwin to invasion eco logy is discussed. Darwin considered biotic invasions as complex but integral phenomena involving ecological, biogeographical, evolutionary, taxonomic and other aspects, such as patterns of past and present distribution, means and pathways of dispersal (and dispersal limitations), struggle for existence and natural selection, phylogenetic relationships of taxa, environmental factors, and evolutionary changes. All modern hypotheses explaining biotic invasions are evolutionary in their nature. Darwin outlined not one naturalization hypothesis but at least three invasion concepts, which may be considered as precursors of modern theories/hypotheses of biotic invasions. Thus, Darwin established foundations for all following evolutionary and ecological studies of biotic invasions, including several currently debated invasion concepts, such as Escape from Enemies, Empty Niche, Species Richness, and Disturbance hypotheses. It is demonstrated that Dar winian explanations of invasions are based on the balance between biotic/abiotic factors and ecological interactions. У статті обговорюється внесок Ч. Дарвіна до концепції екології інвазій. Учений розглядав біотичні інвазії як складний, але комплексний феномен, що охоплює екологічні, біогеографічні, еволюційні, таксономічні та інші аспекти, зокрема особливості сучасного та минулого поширення (і міграційних бар’єрів), боротьбу за існування та природний добір, філогенетичні відносини таксонів, екологічні чинники та еволюційні зміни. Всі сучасні гіпотези біотичних інвазій є, по суті, еволюційними. Дарвін окреслив не одну гіпотезу натуралізації, але принаймні три концепції інвазій, які можна трактувати як попередники сучасних теорій і гіпотез біотичних інвазій. Таким чином, Дарвін заклав підвалини всіх подальших еволюційних та екологічних досліджень біотичних інвазій, включаючи такі сучасні гіпотези інвазій, як «втеча від ворогів», «порожня ніша», «видове багатство» та «порушення». Показано, що Дарвінівські пояснення інвазій ґрунтуються на співвідношенні між біотичними й абіотичними факторами, на інших екологічних взаємодіях. В статье рассматривается вклад Ч. Дарвина в концепцію экологии инвазий. Ученый рассматривал биотические инвазии как сложный, но целостный феномен, который включает экологические, биогеографические, эволюционные, таксономические и другие аспекты, в частности, особенности современного и прошлого распространения (и миграционных барьеров), борьбу за существование и естественный отбор, филогенетические связи таксонов, экологические факторы и эволюционные изменения. Все современные гипотезы биотических инвазий в своей основе являются эволюционными. Дарвин наметил не одну гипотезу натурализации, но, по крайней мере, три концепции инвазий, которые могут рассматриваться как предтечи современных теорий и гипотез биотических инвазий. Таким образом, Дарвин заложил основы всех последующих эволюционных и экологических исследований биотических инвазий, включая такие современные гипотезы инвазий, как «бегство от врагов», «пустая ниша», «видовое богатство» и «нарушенность». Показано, что Дарвиновские пояснения инвазий основываются на соотношении биотических и абиотических факторов и экологических взаимодействиях.